Treatment of opportunistic infections prior to HAART initiation does not affect immune reconstitution in HIV-infected patients - Sakorn Pornprasert (2018)
In patients receiving highly active antiretroviral therapy (HAART), increase of naïve T-cell production, as measured by T-cell receptor rearrangement excision circles (TRECs), is an indicator of immune reconstitution. Our objective was to assess whether treating opportunistic infections (OIs) prior to HAART initiation affects CD4 T-cells recovery and TRECs in patients on HAART. HIV-infected patients presenting no OIs or treated OIs were prospectively enrolled prior to HAART initiation and followed-up over 12 months of HAART. CD4 T-cells and TRECs were measured at baseline, 6 and 12 months HAART and compared between patients presenting no OIs and those with treated OIs. Univariate and multivariate logistic regression models were used to identify potential factors associated with low TREC increase after 12 months HAART. Forty-four HIV-infected patients, 31 presenting no OIs and 13 with treated OIs at HAART initiation were enrolled. Patients presenting no OIs tended to have higher CD4 T-cell gain than those with treated OIs (151 vs 89 cells/μL; p = 0.05) after 6 months HAART but not after 12 months HAART (120 vs 149 cells/μL; p = 0.84). Among patients presenting no OIs, TREC levels significantly increased from baseline through 12 months HAART while among those with treated OIs, there was a trend for increase only after 12 months. Our study indicates that treatment of OIs prior to HAART does not lead to impaired CD4 T-cells recovery and thymic outputs. © 2012 Bentham Science Publishers.